Avaliação do potencial citotóxico de três novos derivados da a-santonina em modelos experimentais in vitro - Ferreira, José Roberto de Oiveira (2009)
The sesquiterpene lactones have different chemical structures, and a variety of biological activities, among which stand out the cytotoxic and antitumour activities. The aim of the present study was to determine the cytotoxic effects of three new α-Santonin (1) derivatives: 3-oxo-7αH,6H-eudesma-1,4,11-trien-6,12-olide (2), 11,13-dehydrolumissantonin (3) and 10α-acetoxi-3-oxo-1,7αH,6H-guai-4,11-dien-6,12-olide (4) and study your effects on cell proliferation, cell cycle, and apoptosis events. All new derivatives inhibited the proliferation of tumor cells, by MTT assay, except the prototype (α-santonina) after 72 h of incubation. The cell lines HL60 (leukemia) and HCT-8 (colon) showed greater sensitivity to treatment with these derivatives, with values of IC50 for HL60 equal to 1.14 (0.23-2.77); 2.30 (1.87-2.84) and 1.60 (1.09-2.35) µM and for HCT-8 equal to 2.92(0.98-4.86); 1.96 (1.64-2.29) and 0.36 (0.16-0.79) µM for compounds 2, 3 and 4, respectively.. Two derivatives were less cytotoxic to peripheral blood mononuclear cells (PBMC): IC50 equal to 10.75 (4.6-23.3) µM (3) and IC50 equal to 16.77 (7.3-36.8) µM (4). However, compound 2 showed lower selectivity (IC50 equal to 3.24 (1.6-5.3) µM) on PBMC. None of the studied compounds induced hemolytic effects. To evaluate the mechanism of action promoted by these derivatives, HL60 cells was chosen as an experimental model, since this linage was one of the most sensitive to treatment. HL60 cultures were treated with α-santonin derivatives (1 and 2 µM) during 24 h. All compounds were able to reduce the number of viable cells evaluated by the trypan blue dye exclusion test at highest concentration, without increasing the number of non-viable cells. The antiproliferative action is related to the ability to inhibit the synthesis of DNA. After treatment, the derivatives were able to induce apoptosis, as observed by cell morphology pattern (chromatin condensation, and nuclear fragmentation), and by flow cytometry (membrane integrity, DNA fragmentation, anexin positive cells, and caspases 3 and 7 activation). None of all derivatives analyzed caused depolarization of mitochondrial membrane, suggesting the involvement of the extrinsic pathway in the apoptotic process. The compounds 3 and 4 induce G2/M cell cycle arrest, indicating a different mechanism of action in relation to compound 2. These data suggest that α-santonin derivatives evaluated in the present study showed a anticancer potential, especially the compound 4, which induced moderate toxicity on PBMC, in addition this compound induced a higher rate of cell death via apoptosis when compared to the other α-santonin derivatives evaluated.